TDOA Geo location estimation techniques - Too, Shang Yao. (2010)
Wireless location estimation has been gaining more recognition in the past two decades. These techniques are important especially for emergency situations as they enable emergency services to locate the distress callers. Techniques include the time of arrival (TOA), the time difference of arrival (TDOA), the angle of arrival (AOA), hybrids and pattern matching methods. Under the TDOA technique, there are various methods such as the spherical intersection, spherical interpolation, divide and conquer, Taylor series, Chan’s method and Fang’s method. In view of the rising demand of wireless Geo Location estimation techniques, this report focuses on the TOA and TDOA methods.